(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: Describe the disease pattern of in-patients at Duc Giang General Hospital, Hanoi in 2024. Materials and methods: A cross-sectional descriptive study, taking all in-patients at Duc Giang General Hospital from January 1, 2024 to December 31, 2024. Results: The total number of in-patients at Duc Giang General Hospital in 2024 was 49,602. Of which, women accounted for 51.8%, the proportion of patients with health insurance was 92.3%. The average age of patients was 45.4 ± 24.8 years old; the age group 60–79 had the highest proportion (35.7%). Non-communicable diseases accounted for the majority (84.9%), the most common being respiratory, musculoskeletal and digestive diseases. The proportions of hypertension, diabetes, spinal pathology and vestibular dysfunction were higher in female patients; pneumonia, kidney and ureteral stones were higher in male patients (p <0.05). Cerebral stroke, colorectal cancer, intestinal infection and sepsis did not differ between the two genders (p >0.05). Some diseases changed over time, with pneumonia being most common in January, hypertension in March and cerebral stroke in July. Conclusion: In-patients treated at Duc Giang General Hospital, Hanoi in 2024 are mostly in the group of non-communicable diseases. There are differences in disease pattern by gender and time of year. This result contributes to the orientation of building management, prevention and medical examination and treatment programs.